2014
DOI: 10.2190/om.69.4.c
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Perfectionism: A Psychological Autopsy Study of Non-Clinical Suicides

Abstract: This study explores suicide in relation to perfectionism among individuals who died by suicide with no history of treatment in mental health care or of suicide attempts. The study is part of an ongoing psychological autopsy study (PA-study). It aimed to produce a phenomenological understanding of the dynamics/processes from perfectionism to suicide among 6 men aged 22 to 58. Interpretative Phenomenological Analysis (IPA) was used to analyze the interview data of 41 key informants. Based on the informants' narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
(33 reference statements)
2
24
0
1
Order By: Relevance
“…Anger [34,42], direct statements of suicidal intent [33,44], and paucity of problem solutions [33,42] were common signs associated with male deaths by suicide (see Table 2). Rasmussen et al [33] also found that in the days prior to death by suicide, many informants reported that conversations with the deceased were marked by an absence of negative mood, or the emergence of a more positive mood state, in addition to agitation, the perception of death as a problem solution, desperation and reaching out for support in desperation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anger [34,42], direct statements of suicidal intent [33,44], and paucity of problem solutions [33,42] were common signs associated with male deaths by suicide (see Table 2). Rasmussen et al [33] also found that in the days prior to death by suicide, many informants reported that conversations with the deceased were marked by an absence of negative mood, or the emergence of a more positive mood state, in addition to agitation, the perception of death as a problem solution, desperation and reaching out for support in desperation.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies identified anger as a suicide sign associated with suicide attempts among men [31,45,46]. A paucity of problem solutions was associated with suicidal ideation [38], but also associated with death by suicide among men[33,42]. Direct statements of suicidal intent were associated with both suicide attempt and death among men[33,44,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 50 years of case reports, theoretical accounts, and empirical research implicate perfectionism in suicide (e.g., Blatt, ; Hassan, Flett, Ganguli, & Hewitt, ; Hewitt et al, ; Kiamanesh, Dyregrov, Haavind, & Dieserud, ; Shaffer, ). And yet, there is much to learn about the perfectionism–suicidality relationship (Flett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Los individuos con perfeccionismo desadaptativo tienen una mayor prevalencia a experimentar síntomas del desorden afectivo, como depresión y ansiedad (Abdi, Gholamreza Chalabianloo, Joorbonyan, 2015;Egan, Wade y Shafran, 2011), y a presentar actitudes y conductas alimentarias de riesgo (Boone, Soenens, Braet, y Goossens, 2010;Dour y Theran, 2011;Sherry, Stoeber y Ramasubbu, 2016), estrategias disfuncionales para enfrentar el estrés (Sirois y Molnar, 2014), adicción al trabajo (Stoeber, Davis y Townley, 2013) e inclinación suicida (Kiamanesh, Dyregrov, Haavind y Dieserud, 2014;Rasmussen, Slish, Wingate, Davidson y Grant, 2012), entre otras características perjudiciales.…”
Section: Introductionunclassified